Pengaruh Disiplin Kerja dan Beban Kerja Terhadap Kinerja Karyawan Pada PT. Bank Mandiri (Persero) Tbk. Kantor Cabang Pembantu Polewali Mandar - Dian Magfira; Agung Widhi Kurniawan; Burhanuddin; Chalid Imran Musa; Tenri S.P. Dipoatmodjo (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2023)
This study aims to determine the effect of work discipline and workload on employee performance at PT. Bank Mandiri (Persero) Tbk. Polewali Mandar Sub-Branch Office. The type of this research is quantitative research. The number of samples in this study were 30 employees. The method applied to collect research data is the questionnaire method. The techniques applied to analyze the research data are validity and reliability tests, multiple regression analysis, classic assumption test, t test and F test. This research shows positive results between work discipline variables (X1) and workload (X2) on employee performance (Y) which is shown through the multiple linear regression equation, namely Y = 14,229 + 0.401 + 0.358. In the t test with the work discipline variable (X1) it shows a t count of 2.091 and a t table of 2.051 and a sig. 0.046 <0.05. Workload (X2) has a t count of 2,832 and a sig value of 2,051 t table. 0.009 <0.05. The f test shows f count 6.662 and f table 3.3340 and sig. 0.004 <0.05. Based on the description, it can be concluded that partially work discipline has an effective effect which is very significant on employee performance, partially workload has a significant positive effect on employee performance. Work discipline and workload have a simultaneous and significant influence on employee performance.